Processing and mechanical characteristics of magnesium-hydroxyapatite metal matrix biocomposites. (May 2017) - del Campo, R.; Savoini, B.; Muñoz, A.; Monge, M.A.; Pareja, R.
Abstract: Magnesium/hydroxyapatite composites were produced by conventional extrusion and their mechanical behavior studied under uniaxial compression at room temperature. The results evidence the capability of the HA for strengthening the Mg material, lowering its microstructural anisotropy and inhibiting deformation twinning. They also reveal that the ECAP processing is effective for improving the grain structure and reducing the crystallographic texture of these composites, giving rise to a significant enhancement of their yield strength and microhardness although the ultimate compressive stress worsens. The analysis of the strain hardening rate of the flow curves demonstrates that the HA addition and the ECAP processing are also effective in inhibiting non-basal dislocation slip. Graphical abstract: Highlights: Mg-HAP composites were produced by a powder metallurgy followed by extrusion and ECAP. The HAP addition to Mg enhances compressive strength, reduces extrusion texture and prevents deformation twinning. ECAP deformation of these composites destroys the initial texture and improves yield strength and microhardness. A lineal correlation is found between athermal strain hardening rate and inverse of texture index.